تأثير التكوين الجامعي، الإعلام، المعايير الذاتية في نية إنشاء مشروع في المجال الرياضي - Nasri,mohamed cherif; Tiaibia,fouzi; Ababsa,houssameddine (مجلة التنويل والاصتجنار والتهنية المضتدامة, 2022)
هدفت الدراسة الى التعرف على تأثير كل من التكوين الجامعي ، الاعلام ، المعايير الذاتية على نية انشاء مشروع في المجال الرياضي لدى طلبة علوم الرياضة ،و لهذا الغرض تم اختيار عينة عشوائية طبقية قدرت بـ 156 طالب موزعين على ثلاث معاهد مختلفة و هي معهد المسيلة ،الاغواط ،ام البواقي ،و هذا باستخدام استبيان اعد لهذا الغرض و يتكون من 21 عبارة .و قد تم تحليل البيانات باستخدام الانحدار الخطي البسيط و المتعدد .و توصلت الدراسة الى ان العوامل الثلاثة تؤثر في نية طلبة علوم الرياضة في انشاء مشروع في المجال الرياضي ،كما ان تأثيرها مجتمعة يحسن قدرة النموذج أفضل من تأثير كل عامل على حدا ،و كانت المعايير الذاتية أكثر العوامل تأثيرا يليها التكوين الجامعي ثم الاعلام . The study aimed to knew the effect of university formation, media and subjective norms to create a project in the sports field within sports sciences students, therefore a sample of 156 students was arbitrarily and stratified chosen and distributed in three different institutes: M’sila, Laghouat and Oum El Bouaghi through a questionnaire of21 expressions prepared for this purpose. Data were analyzed by a simple and multiple linear decline. this study reached to a result that the three factors have an effect on the intention of sports sciences students in creating a project in the sports field and its effect all together improve the ability of the model better than the effect of each factor alone and the most effective factor was the subjective norms then the university formation and finally the media